Liquid level control in two tanks spherical interacting system with fractional order proportional integral derivative controller using hybrid technique: A hybrid technique. (January 2023) - Arivalahan, R.; Tamilarasan, P.; Kamalakannan, M.
Highlights: Liquid level control in two tanks spherical interacting system (TTSIS) with FOPID. Chaotic Henry gas solubility optimization and feedback artificial tree. FOPID controller is modeled for a spherical tank's liquid level control. The spherical tank system is important in nonlinear operation. FOPID controller is used to tune the system parameters. Abstract: This paper proposes a Liquid Level Control in two tanks spherical interacting system (TTSIS) with Fractional Order Proportional Integral Derivative (FOPID) controller using hybrid system. The proposed approach is the consolidation of chaotic Henry gas solubility optimization (CHGSO) and Feedback Artificial tree (FAT), and later it is known as CHGSO-FAT technique. The FOPID controller is modeled as Fractional Order System for a spherical tank's liquid level control. The Spherical tank system is important in nonlinear operation, because its variation on the radius of tank and the interaction of the two tanks with FOPID sliding surface. Moreover, FOPID controller is proposed the system output is directly used to tune the system parameters. The proposed controller is enhanced by increasing the fractional values of the derivative term FOPID sliding surface. The performance indices, as settling time, rise time, peak overshoot and peak time is analyzed. The proposed system is performed on MATLAB/Simulink working platform. The mean, median and standard deviation for 100 iterations with proposed system is 0.338, 0.4173 and 0.00334.